Hubungan Penghasilan, Kelompok Umur, Tingkat Pendidikan dan Status Pekerjaan Terhadap Kepemilikan Asuransi Kesehatan di Kota Bogor - Eka Putri Rahayu; M. Zakki Saefurrohim (Institut Kesehatan dan Teknologi Al Insyirah, 2025)
A Health insurance is a form of insurance designed to ease the financial burden due to changes in health. As of Q1 2023, Indonesia has 136 insurance companies consisting of 2 social insurance, 2 mandatory insurance, 72 general insurance, 53 life insurance and 7 reinsurance companies. The percentage of Bogor city residents who have health insurance in the form of BPJS health is 56.49%, Jamkesda/private insurance/Company is 7.91% in 2021. The absence of health insurance can be a poverty trap. In addition, the absence of health insurance will affect the utilization of health services, health expenditure and health status. This study aims to determine the relationship between income, age group, education level and employment status to health insurance ownership in the city of Bogor. This study is a further analysis by utilizing data from the Cohort Study of Non-Communicable Disease Risk Factors (NCDs) in Bogor City in 2018 from the Ministry of Health of the Republic of Indonesia. The design of this study is Cross Sectional. Respondents registered in the 2018 Bogor City NCD cohort study amounted to 3,784 respondents with the analysis test used was Chi Square. Ownership of health insurance in Bogor City is significantly influenced by income, age group, education level, and employment status, with each variable having a p-value <0.05. The results of this study can be the basis for developing more effective policies and programs to improve access to health services and community welfare